Community Perception on Flats Development as a Living House in Urban Area, Singosari Sub-District, Malang Regency - Halim, Lusiani Ferelia; Rachmansyah, Arief; Soemarno, Soemarno (Jurnal Pembangunan dan Alam Lestari, 2025)
The increase in land limitation as a living space triggered the higher price in the Malang area, thus becoming unaffordable for low-income communities. This problem causes the shift of land choices to the border area, as happened in the Singosari sub-district. But unfortunately, the trend of housing as a current model of housing development will impact the reduction of land space, land conversion, slums, reduced water catchment area, etc. The development of flats is considered to be more appropriate for the sustainable development concept. This study aims to determine the community interest and to know the level of economic affordability for the development of a flats model, especially for low-income communities in Singosari. To support this research, we made 2 designs of flat buildings. This research was conducted at Bumi Mondoroko Raya housing (37.62 Ha). This housing focuses on providing living housing for low-income communities.  We use a descriptive qualitative method and quantitative methods through the distribution of questionnaires. The result shows that the community can not accept the house with the flats model, although they can reach the selling price of flats as 95.24% economically by utilizing the subsidized mortgage for 20 years. Keywords: Flats, Low Income Community, Interest